Tailored Light 2 Laser Application Technology - Poprawe, Reinhart; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The present book covers the application technology of lasers, focusing more on the vast range of processes than on individual applications, in order to motivate and enable future innovations. The physical basics are presented in the first half of the book. The following examination of application categories and their processes is documented by experts from their practical points of view but always refers back to the underlying physical principles. In this way, readers are free to choose their own individual level of depth in understanding this globally relevant field of innovation.
Preface -- Introduction -- Radiation at interfaces -- Absorption of Laser Radiation -- Energy Transport and Heat Conduction -- Thermo Mechanics -- Phase Transformations -- Melt Flow -- Laser Induced Vaporization -- Plasma Physics -- Laser Beam Sources -- Surface Treatment -- Forming -- Rapid Prototyping & Rapid Tooling -- Joining -- Ablation -- Drilling -- Cutting -- System Technology -- Laser Measurement Technology -- Appendix -- Subject index.
Keywords: Engineering; Mechanical engineering; Structural control (Engineering).; Surfaces (Physics).; Engineering; Operating Procedures, Materials Treatment; Characterization and Evaluation of Materials; Engineering, general; Mechanical Engineering